Attitude Processes and User Experiences in Virtual Reality Simulations : Attitude Transitions in Immersive and Non-Virtualized Virtual Reality Machine Gun Simulators - Bhuiyan, Fairuz (My University, 2024)
The study aims to measure attitude processes when using simulators and subjective experiences after use by comparing a VR-based immersive simulator and a classic non-immersive simulator. The target groups are the conscripts in the Parola Armored Brigade of the Finnish Defense Forces, who will receive training in using an anti-aircraft machine gun with the help of virtual reality. Both simulators highlighted commendable traits, such as prompt responsiveness to user actions and awareness of control devices. The VR simulator's propensity to induce more pronounced simulator sickness symptoms occurred similarly in both simulators, suggesting common physiological responses across different simulator types. Interestingly, participants in the VR simulator found it easier to control events and manipulate objects, leading to better engagement than in real-life scenarios. These findings illuminate the advantages and limitations of VR training with augmented cues, offering valuable insights for refinement and future research endeavors.

Tutkimuksen tavoitteena on mitata asenneprosesseja simulaattoreiden käytössä ja subjektiivisia kokemuksia käytön jälkeen vertaamalla VR-pohjaista immersiivistä simulaattoria klassiseen ei-immersiiviseen simulaattoriin. Kohderyhmiä ovat Puolustusvoimien Parolan panssariprikaatin varusmiehet, jotka saavat koulutusta ilmatorjuntakonekiväärin käyttöön virtuaalitodellisuuden avulla. Molemmat simulaattorit korostivat kiitettavia piirteitä, kuten nopea reagointi käyttäjän toimiin ja tietoisuus ohjauslaitteista. VR-simulaattorin taipumus aiheuttaa selvempiä simulaattorisairausoireita esiintyi samalla tavalla molemmissa simulaattoreissa, mikä viittaa yhteisiin fysiologisiin vasteisiin eri simulaattorityypeissä. Mielenkiintoista on, että VR-simulaattoriin osallistuneiden oli helpompi hallita tapahtumia ja käsitellä esineitä, mikä johti parempaan sitoutumiseen kuin tosielämän skenaarioissa. Nämä havainnot valaisevat VR-harjoittelun etuja ja rajoituksia laajennetuilla vihjeillä ja tarjoavat arvokkaita oivalluksia jalostukseen ja tuleviin tutkimushankkeisiin.
Keywords: simulator, VR-based, immersive, non-immersive, virtual reality, user experience, training, anti-aircraft, machine gun, responsiveness, control devices, sensory feedback, user-friendly